PENGARUH EFEKTIVITAS PENERAPAN TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH - Widarsono, Agus (Jurnal Riset Akuntansi dan Keuangan, 2013)
This research has purposes to know how the impact of the effectiveness of the technology information application to the quality of financial report in the regency area governance. This methods used into this research is verification descriptive. The data collected by spreading questioners that use semantic defferensial scale on its scoring. To assess the impact of effectiveness of the application of information technology (X) to the quality of financial report (Y), then used simple linear regression. Where as to know how much the impact that is given to the variable of independence, then use coefficient of determination. The result of the analysis shows that the applied of effectiveness information technology has positive impact to the quality of financial report in regency governance. Effectiveness of the application of information technology give impact 53,0% to the quality of financial report of the official regency governance, the agency and office in the environment of Sukabumi regency. While the rest 47,0% is the impact of another factors outside effectiveness of the application of information technology.